Validitas Modul Ajar Pola Pewarisan Sifat pada Hukum Mendel Berbasis Problem Based Learning - Welly Junengsih; Syamsurizal Syamsurizal; Fitri Arsih; Suci Fajrina (ISLAMIKA, 2023)
The implementation of the independent curriculum requires teachers to develop teaching tools in the form of complete and systematic teaching modules. This study aims to produce a valid Mendelian law of inheritance patterns teaching modules. The research method is R&D (Research and development) with the 4D development model. The subjects of this study were two biology lecturers at FMIPA UNP and six biology teachers. The data collection instruments were observation questionnaires, validity questionnaires, and legibility test questionnaires. This study found that the independent curriculum teaching modules in phase F were not yet available because the independent curriculum had just been implemented. Based on the research conducted, it was found that the teaching module on the pattern of inheritance on Mendel's laws based on problem based learning for biology subjects in phase F SMA/MA is valid with an average score of 91.20% and very valid criteria.